Tuck-in deep anterior lamellar keratoplasty for the management of post-radial keratotomy keratectasia. Issue 8 (August 2022) - Nagpal, Ritu; Sharma, Namrata; Bafna, Rahul Kumar; Muraleekrishna, Manu; Vajpayee, Rasik Bihari
Abstract : Tuck-in DALK can successfully address corneal ectasia developing after RK. Abstract : Purpose: To evaluate the outcomes of tuck-in deep anterior lamellar keratoplasty (DALK) for the management of post-radial keratotomy (RK) keratectasia. Setting: Institution. Design: Retrospective. Methods: Medical records of all cases presenting with post-RK keratectasia from January 2012 to December 2019 were included. Data on corrected distance visual acuity (CDVA), refraction, keratometry, ultrasonic pachymetry, corneal topography, endothelial cell count, applanation tonometry, and dilated fundus examination recorded at all follow-up visits were included. Details of surgical steps, including intraoperative and postoperative complications and any secondary procedures performed subsequently, were also recorded. Results: 7 eyes of 5 patients that developed corneal ectasia after a previous RK procedure underwent DALK with peripheral tuck-in. All eyes had CDVA ≤6/24, preoperatively. The surgical procedure was successfully performed in all eyes without any intraoperative complications. CDVA at the final follow-up ranged between 6/9 and 6/60, with 6 eyes achieving CDVA of 6/18 or better. The median keratometric cylinder reduced from a preoperative value of 7.2 ± 9.27 diopters (D) to 2 ± 1.83 D at the final follow-up. The median central corneal thickness at the final follow-up was 598 ± 40.01 μm, and spherical equivalent ranged between −1.75 D and −3.5 D (median −2 ± 0.57). The percentage of endothelial cell loss ranged between 2.1% and 8.4%. All eyes retained graft clarity, and none showed any evidence of significant interface haze or corneal vascularization. Conclusions: Tuck-in DALK could successfully address corneal ectasia developing after RK, achieving visual gains. Moreover, it was able to restore the peripheral corneal thickness with a minimal risk for dehiscence of RK incisions.